1988
DOI: 10.1104/pp.88.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Protoplast Viability of Suspension-Cultured Rice Cells during Isolation Process

Abstract: Callus cells of rice (Oryza sativa L.) that were actively dividing in suspension culture had lost the ability to divide during the isolation process of protoplasts. Factors influencing the protoplast viability were examined using highly purified preparations of cellulase C,, xylanase, and pectin lyase, which were essential enzymes for the isolation of protoplasts from the rice cells. The treatment of the cells with xylanase and pectin lyase, both of which are macerating enzymes, caused cellular damage. Xylanas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
1
12

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 23 publications
3
28
1
12
Order By: Relevance
“…Nevertheless, it should be remembered that for technical reasons (depth of focus of the objective used [6,9,15] or probe internalization [13]), it is extremely difficult to assess that the fluorescence signal which is observed originates only from the plasma membrane. From another point of view, it has been shown that protoplast preparation through enzymic degradation of the cell wall, as usually done, can be damaging for the protoplast itself, either in terms of cell viability (8) or with respect to the structure of the plasma membrane (5) or its lipid composition (2). In addition, production of activated oxygen in the form of superoxide radical 2-has been reported in the course of preparation of protoplasts from rice cells when using macerating enzymes (8).…”
Section: Lateral Diffusion Of Fluorescent Probes In Vacuolar Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it should be remembered that for technical reasons (depth of focus of the objective used [6,9,15] or probe internalization [13]), it is extremely difficult to assess that the fluorescence signal which is observed originates only from the plasma membrane. From another point of view, it has been shown that protoplast preparation through enzymic degradation of the cell wall, as usually done, can be damaging for the protoplast itself, either in terms of cell viability (8) or with respect to the structure of the plasma membrane (5) or its lipid composition (2). In addition, production of activated oxygen in the form of superoxide radical 2-has been reported in the course of preparation of protoplasts from rice cells when using macerating enzymes (8).…”
Section: Lateral Diffusion Of Fluorescent Probes In Vacuolar Membranementioning
confidence: 99%
“…From another point of view, it has been shown that protoplast preparation through enzymic degradation of the cell wall, as usually done, can be damaging for the protoplast itself, either in terms of cell viability (8) or with respect to the structure of the plasma membrane (5) or its lipid composition (2). In addition, production of activated oxygen in the form of superoxide radical 2-has been reported in the course of preparation of protoplasts from rice cells when using macerating enzymes (8). The possibility of degradation of phospholipid-like probes (such as NBD-PC) by phospholipases (12) also should not be ignored.…”
Section: Lateral Diffusion Of Fluorescent Probes In Vacuolar Membranementioning
confidence: 99%
“…Subsequent work has shown that the enzyme from T. viride also elicits other defense responses in tobacco, including synthesis of pathogenesisrelated proteins (18), tissue necrosis, and electrolyte leakage (3). Other fungal endoxylanases have been shown to elicit defense responses, such as phytoalexin production (10), lipid peroxidation (13), vascular gelling (29), and cell death (5), in various plant tissues. However, with the exception of the enzyme from Phytophthora parasitica f. sp.…”
mentioning
confidence: 99%
“…Recently, Ishi (13) demonstrated that a macerating xylanase isolated from a commercial preparation of T. viride origin was toxic to rice cell cultures. Lotan and Fluhr ( 16) observed the induction of pathogeniesis-related proteins (i.e.…”
mentioning
confidence: 99%